Gravitationally induced adiabatic particle production: from big bang to de Sitter. (27th July 2016) - Haro, Jaume de; Pan, Supriya
Abstract: In the background of a flat homogeneous and isotropic space–time, we consider a scenario of the Universe driven by the gravitationally induced 'adiabatic' particle production with constant creation rate. We have shown that this Universe attains a big bang singularity in the past and at late-time it asymptotically becomes de Sitter. To clarify this model Universe, we performed a dynamical analysis and found that the Universe attains a thermodynamic equilibrium in this late de Sitter phase. Finally, for the first time, we have discussed the possible effects of 'adiabatic' particle creations in the context of loop quantum cosmology.